Radikalisme Islam, Pembangunan Perdamaian dan Dialog Antar Agama di Papua Indonesia - Ridwan, Ridwan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
The objective of this study is to analyze the growth of radicalism, peacebuilding, and the role of inter-religious dialogue in Papua from a broader perspective. This paper argues that the Religious Harmony Forum (FKUB) and the Religious Leaders Communication Forum (FKPPA) have succeeded in maintaining harmony in Papua. However, the threat of religious radicalism remains an issue in the complexity of the political conflicts that occur. The Harmony Integrity Zone model in Jayapura district is an effort of inter-religious dialogue that is good enough to be replicated with modifications in other places. This paper is the result of a desk-study to fill the academic gap in transnational Islamic studies in the Land of Papua, a study that has not been explicated by researchers in the past.